A Translation Analysis of English Modal Verb in The House of Hades Novel into Gerha Hades by Rika Iffati Fahira - Wulandari, Ajeng Wahyu, Dr. Dwi Haryanti, M.Hum, Siti Fatimah, S. Pd, M. Hum (2015)
The research paper analyzes English modal verb in translation The House of Hades novel. The study aims (1) to identify translation variations of English modal verb found in The House of Hades novel and (2) to describe the accuracy translation of English modal verb found in The House of Hades novel.The type of this research is descriptive qualitative research. The object of the study is the novel entitled The House of Hades and its translation. The data of this study is English modal verb in The House of Hades novel. Data source used in this research are the documentation of the data research paper and the informant or one rater. The researcher uses document and questionnaire in collecting data. The data are analyzed by using comparing method.Based on the analysis, there are 4 types of English modal verb. 36 data or 6,7% of English modal verbs translated into Indonesian adverb. English modal verb translation variation has 31 data or 5,8% of translated into Indonesian adjective, English modal verb translated into Indonesian modal verbs translation variation has 417 data or 77,5%, Deletion has 54 data or 10%. So, it finds 538 data or 100% in translation variation.In their accuracy, , from 538 English modal verb there are 476 data or 88,5% accurate, 12 data or 2,2% less accurate and 50 data or 9,3% not accurate. It can be concluded that from 538 data English modal verb translation variations are accurate.